PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK-PAIRSHARE (TPS) TERHADAP KETERAMPILAN BERPIKIR KRITIS SISWA KELAS V SEKOLAH DASAR - Mega Astuti, Dita; Ayurachmawati, Puji; Marhamah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the Think-Pair-Share (TPS) cooperative learning model on students’ critical thinking skills in the IPAS curriculum for fifth grade, Chapter 8, “My Beloved Earth, My Poor Earth,” specifically regarding the types of waste and methods of waste management. This study was motivated by the low level of critical thinking skills among fifth-grade students at SDN 005 Palembang. The research method used was a quasi-experimental design with a nonequivalent control group design, consisting of two groups: an experimental class and a control class. The research sample consisted of all fifth-grade classes, namely VA and VB. The average posttest score for the experimental class was 84.57, while the control class scored only 76.96; thus, it can be concluded that the Think-Pair-Share (TPS) cooperative learning model has an effect on students’ critical thinking skills. The results of the independent samples t-test, assuming equal variances, yielded a significance value (Sig., 2-tailed) of 0.000 < 0.05. This indicates that the null hypothesis (HO) is rejected and the alternative hypothesis (Ha) is accepted, meaning there is a significant difference between the experimental and control groups. Thus, it can be concluded that the use of the Think-Pair-Share (TPS) cooperative learning model has an effect on critical thinking skills.